Eugenia Drakopoulou, Εικόνες του Αγώνα στην ιστορική ζωγραφική της Ευρώπης [Images of the Greek War of Independence in European history painting] - Kouria, Aphrodite (The Historical Review/La Revue Historique, 2023)
Review of Eugenia Drakopoulou, Εικόνες του Αγώνα στην ιστορική ζωγραφική της Ευρώπης [Images of the Greek War of Independence in European history painting]